Disaggregated Analysis of the Effects of Energy Consumption on Greenhouse Gas Emissions in Africa - Guedie, Rolly; Ngnemadon, Ali Salim Ahmed; Fotio, Hervé Kaffo; Nembot, Luc (Energy Economics Letters, 2022)
This study investigates the effect of energy consumption on greenhouse gas (GHG) emissions in 33 African countries from 1995–2017. It contributes to the literature by investigating the effect of disaggregated measures of energy consumption (coal, oil and other liquids, renewable energy, and electricity) on GHG emissions (CO2, N2O, CH4, and total GHG emissions) in Africa and identifies the transmission channels through which energy consumption affects GHG emissions. The system GMM is used in the study as it accounts for possible endogeneity and the potential correlation between the error term and the country fixed effects. The results show that coal consumption significantly increases CO2, CH4, and total GHG emissions and reduces N2O emissions. Oil consumption increases CO2 and total GHG emissions but reduces N2O and CH4 emissions. Renewable energy consumption reduces CO2 and CH4 emissions but increases N2O emissions. Finally, electricity consumption promotes CO2, N2O, CH4 and total GHG emissions in Africa. Further analyses show that foreign trade and economic growth are the channels through which oil consumption increases GHG emissions. The adverse effect of electricity is through urbanization. Renewable consumption could decrease GHG emissions through sustainable urbanization and trade policies. The findings suggest that countries should gradually reduce coal consumption and encourage renewable energy consumption, which has the lowest impact on the environment.